Composição florística de angiospermas no carste do Alto São Francisco, Minas Gerais, Brasil - Melo, Pablo Hendrigo Alves de; Lombardi, Julio Antonio [UNESP]; Salino, Alexandre; Carvalho, Douglas Antônio de (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2013)
The occurence of carbonatic rocks defines a typical type of relief, called karst, that, by its geomorphology and hydrology, usually differs from the surrounding landscape. In the upper São Francisco river basin, some striking remnants of vegetation associated to karst can be found, which are locally knwon as Mata de Pains. In this region, a mosaic of different physiognomies, including forests and open areas, which present noteworthy plant diversity, composes the vegetation. The aim of this study is to provide an inventory of angiosperm species in areas of carbonatic rocks outcrops in the upper São Francisco river basin karst region, as well as analyze the floristic relationship of the study area with different Brazilian phytogeographic domains. Fieldwork was performed during the period of 2002 a 2006, when collections of fertile speciemns were done in areas associated to carbonatic rock outcrops. During the study, 1512 exsicates were incorporated to BHCB herbarium collection. A total of 456 angiosperm species were inventoried, distributed in 299 genera and 77 families. Herbaceous habit was better represented, with 161 species, followed by shrubs and trees (111 species each) and lianas (73 species). The flora of the study area presents more influence of the Mata Atlântica domain (Atlantic Rain Forest), followed by, in order of importance, Cerrado, Amazonia, Caatinga, Pantanal and Pampa. Floristic surveys in different karst regions inserted in different phytogeographic domains may, together, provide useful information in understanding the phytogeografic history of Neotropical vegetation.

A ocorrência de rochas carbonáticas delimita um tipo particular de relevo, o carste, o qual, pela geomorfologia e hidrologia específicas, difere das paisagens dominantes. Na região cárstica do Alto São Francisco, conhecida como Mata de Pains, encontram-se exemplos marcantes de relevos cársticos ocorrentes em Minas Gerais. No cárste, a cobertura vegetal é composta por mosaico fitofisionômico apresentando áreas florestadas e áreas abertas, com notável diversidade florística. O objetivo deste estudo foi realizar o levantamento das espécies de angiospermas em áreas com afloramentos de rocha carbonática na Região Cárstica do Alto São Francisco, bem como verificar a relação florística da região estudada com a flora dos domínios fitogeográficos brasileiros. Para o levantamento, no período de 2002 a 2006, foram realizadas expedições mensais para coletas de material botânico fértil concentradas em áreas relacionadas a rochas carbonáticas. O material coletado totalizou 1.512 exsicatas e foi incorporado ao acervo do herbário BHCB. Foram encontradas 456 espécies de angiospermas, distribuídas em 299 gêneros e 77 famílias. O hábito herbáceo foi o melhor representado, com 161 espécies, seguido dos hábitos arbustivo e arbóreo (111 espécies cada), escandente (73 espécies). A flora encontrada na Mata de Pains apresenta influências, em ordem de importância, dos domínios fitogeográficos Mata Atlântica, Cerrado, Amazônia, Caatinga, Pantanal e Pampa. Inventários florísticos em regiões cársticas nos diferentes domínios fitogeográficos podem, em conjunto, fornecer informações importantes no entendimento histórico da vegetação neotropical.
Floristic composition of angiosperms in the karst of upper São Francisco river, Minas Gerais state, Brazil
Keywords: flora; domínios fitogeográficos; Mata de Pains; calcário; dolomito; flora; phytogeographic domains; Mata de Pains; limestone outcrops; dolomite